A Nonradioactive Fluorimetric SPE-Based Ceramide Kinase Assay Using NBD-C6-Ceramide. (26th July 2012) - Van Overloop, Helena; Van der Hoeven, Gerd; Van Veldhoven, Paul P.
Abstract : Ceramide kinase (CERK) has been implicated in important cellular processes such as inflammation and apoptosis. Its activity is usually measured using radiolabeled ceramide or [ γ - 32 P]-ATP, followed by extraction, thin-layer chromatography, and detection of the formed labeled ceramide-1-phosphate. To eliminate the use of radioactivity, we developed similarly but independently from the approach by Don and Rosen (2008), a fluorescence-based ceramide kinase assay, using N-[7-(4-nitrobenz-2-oxa-1, 3-diazole)]-6-aminohexanoyl-sphingenine (NBD-C 6 -ceramide) as substrate. Its K m value (4 μ M) was comparable to that of N-hexanoyl-sphingenine (C 6 -ceramide). The produced fluorescent NBD-C 6 -ceramide-1-phosphate was captured by means of solid-phase extraction on an aminopropyl phase, resulting in a fast and sensitive CERK measurement. By performing this assay in a 96-well format, it is also suitable for high-throughput screening (HTS) to search for CERK modulators. A limited screen revealed that some protein kinase inhibitors (e.g., U-0126; IC 50 4 μ M) and ceramide analogues (e.g., fenretinide, AMG-9810; IC 50 1.1 μ M) affect CERK in vitro .